Bean production and the constraints to production in the highlands areas of Uganda - Kisakye, J. (International Center for Tropical Agriculture, 1991)
The bean producing highland areas of Uganda include the Kabale Mountains and foothills, Mount Elgon, and the southwestern volcanic mountains and foothills of the Rwenzori range. The major constraints to bean production in the highland areas include land degradation, crop diseases and pests, weeds, unavailability of labour, and poor marketing facilities. (AS)